Military service as part of Serbian ethos - Stanar, Dragan; Starčević, Srđan (Sociološki pregled, 2024)
This paper aims to describe and explain why mandatory military service represents the optimal military model in the Republic of Serbia, from the insufficiently explored perspective of the position and nature of the military in Serbian national ethos. The authors analyze the previously provided key arguments for conscription and, furthermore, identify the characteristics of Serbian collective ethos in order to precisely define the role and nature of the military constituted by the accumulated Serbian historical experience. By comparing different contemporary models of armed forces, their advantages, disadvantages, implications and social nature, the authors conclude that conscription is compatible with Serbian national ethos and the characteristics of Serbian national identity and that, as such, it represents the optimal military model in the Republic of Serbia.
Keywords: military service; national ethos; identity; state; military